Challenges in treatment of postinfarction ventricular septal defect and heart failure - Mangovski, Ljupčo; Kozlik-Feldmann, Rainer; Perić, Miodrag; Jovović, Ljiljana; Farkić, Mihajlo; Dekić, Dragica (Vojnosanitetski pregled, 2014)
Introduction. Acquired ventricular septal defect (VSD) is uncommon, but serious mechanical complication of acute myocardial infarction with poor outcome and high mortality rate in surgically or medically treated patients. Case report. We report a 58-year-old male patient admitted to our hospital six days following acute inferior myocardial infarction complicated by ventricular septal rupture with signs of heart failure. Coronary angiography revealed 3-vessel disease, with proximally occluded dominant right coronary artery. Transthoracic echo exam revealed aneurysm of a very thin inferior septum and the basal portion of the inferior left ventricular wall, with septal wall rupture. One of the VSD dimensions was 15 mm and left- to right shunt was calculated 2 : 1. Since the patient was at too high risk for surgical closure, transcatheter closure of VSD was chosen as a better option. Under short intravenous sedation, 24 mm Amplatzer device was implanted percutaneously with transesophageal echo guidance. The post-procedural result revealed a small residual shunt, but it was followed by significant improvement of the patient’s clinical status. A 24h Holter ECG monitoring did not show cardiac rhythm or conduction disturbances. Coronary angiography was repeated ten days following the procedure, after hemodynamic stabilization of the patient, with direct stenting of the circumflex artery and the intermediate artery. Ostial left descending artery lesion was left for further functional significance assessment. Conclusion: Percutaneous closure with a septal occluder device can be definitive primary treatment for anatomically suitable patients or it can serve as a bridge to surgical treatment.
Keywords: myocardial infarction; heart; septal defects; ventricular; heart failure; heart catheterization; treatment outcome